In-Silico Screening of Phytocompounds of Justicia Adhatoda for Thrombolytic Activity - Pushkala, V. Poorna; Subhashree, H.; Yazhini, K. (International Journal of Membrane Science and Technology, 2023)
Background: The risk of thrombosis and its associated mortality is becoming a greater public health concern in both industrialized and developing nations. Clinical condition that is myocardial infarction, ischemic stroke, unstable angina, peripheral vascular diseases like deep vein thrombosis prioritise top in the list of thrombotic disorders. Conventional thrombolytic medications including alteplase, anistreplase, streptokinase and urokinase offer life risking adverse effects like haemorrhage, stroke, vascular dysfunction, hypertension, internal bleeding and so on. In order to overcome the undesirable side effects caused by the conventional thrombolytic therapy, there is ominous need of alternate complementary treatment from traditional medicine. Majority of the Siddha formulations comprise of some potential medicinal herbs which are found to be biocompatible and also have a wide safety window. Justicia adhatoda is one such novel herb which is investigated broadly by researchers till date, aspired by its unique pharmacological property rendered by the bioactive components present in it. Methods: Hence, the present research is aimed at in-silico screening of certain classes of alkaloids and flavonoids retrieved from J. adhatoda to explore the possible anti-thrombotic activity against the target human plasminogen activation loop peptide using AutoDock screening tool. Results and Conclusion: The computational analysis’s findings led to the conclusion that the bioactive compounds present in Justicia adhatoda like Astragalin, Kaempferol, Vitexin, Vasicolinone and Adhatodine reveals significant binding affinity against target plasminogen. Thereby it was determined that these compounds may have promising anti-thrombotic efficacy due to their considerable binding affinity towards the target plasminogen.